Analysis of Age Transformer Due to Annual Load Growth in 20 kV Distribution Network - Roza, Indra; Ananda, Yussa; Siregar, Lisa Adriana; Cahyadi, Catra Indra; Junaidi, Junaidi (Institute for Research and Community Service, Universitas Malikussaleh, Indonesia, 2021)
Distribution transformer is a component in distributing electricity from distribution substations to consumers. Damage to distribution transformers causes continuity of customer service to be disrupted (power cut or blackout occurs). The length of the PLN electricity network requires a transformer to distribute electricity to serve consumers and how to maintain the transformer. The daily load curve of a peak load for housing, shops and factories / industries varies. Load served 200 kVA distribution transformer cannot serve the load on housing, shops and factories / industry. The method used is the replacement of a distribution transformer with a capacity of one stage greater or the replacement of a distribution transformer with a capacity of two levels larger. The distribution transformer carried out by the research is a capacity of 200 kVA replaced by 250 kVA. The ability of a distribution transformer cannot accommodate a load which will increase as an area is advanced. Observations made by calculating the age of the transformer by assuming the annual load growth (r) = 3% = 0.3. Annual peak load (P) = 1.8 p, u increase in oil temperature at peak load (Î¸o = 96.21 0C; 84.16 0C). The increase in the hottest temperature above the oil cover, the increase in the temperature of the hottest place above the oil (Î¸g = 20 0C; 20 0C). The ratio of the load loss to the nominal load excitation loss (Q = 3; 30). By assuming the values of these methods it can be estimated that the life of a distribution transformer is 20 kV, a capacity of 200 kVA is 18 years.